2007
DOI: 10.1111/j.1525-1438.2007.00803.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of different types of treatment in FIGO stage IB2 cervical cancer in Korea: results of a multicenter retrospective Korean study (KGOG-1005)

Abstract: The purpose of this study is to review FIGO stage IB2 cervical cancers in Korea for the past 10 years, and evaluate the most frequently employed and appropriate management strategy, and also assess the survival benefits of neoadjuvant chemotherapy (NAC). This is a retrospective chart review of 727 FIGO stage IB2 patients from 1995 to 2005. Six hundred ninety-two patients were enrolled, and all dates on which the patients died were double checked through the "National Registry of Death Statistics" of the Korea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 24 publications
4
24
0
Order By: Relevance
“…Additionally, a published meta‐analysis shows that NACT followed by surgery is superior to radiotherapy alone in terms of overall survival 5. Because of these advantages, NACT is used in up to 25% of cervical cancer patients in many parts of the world, such as Asia, Italy, and South America 6. On the other hand, there are several objections because for patients with locally advanced cervical cancer (LACC) who do not response to NACT, the delay in curative treatment, the development of radio‐resistant cellular clones and cross‐resistance with radiotherapy may exert negative impact on patient survival 7.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a published meta‐analysis shows that NACT followed by surgery is superior to radiotherapy alone in terms of overall survival 5. Because of these advantages, NACT is used in up to 25% of cervical cancer patients in many parts of the world, such as Asia, Italy, and South America 6. On the other hand, there are several objections because for patients with locally advanced cervical cancer (LACC) who do not response to NACT, the delay in curative treatment, the development of radio‐resistant cellular clones and cross‐resistance with radiotherapy may exert negative impact on patient survival 7.…”
Section: Introductionmentioning
confidence: 99%
“…37 This report concluded that survival rates were the best among patients who underwent postoperative adjuvant CCRT, while the worst in radiotherapy only. Since 2005, the KGOG has been conducting a prospective study in an attempt to ascertain the effectiveness of paclitaxel and carboplatin as a CCRT regimen for patients with high risk factors for recurrent disease after radical hysterectomy.…”
Section: Primary Ccrt In Locally Advanced Cervical Cancer Hee Sug Ryumentioning
confidence: 94%
“…Although not recommended as a standard therapy, this approach is employed in about 25% of patients with locally advanced tumors. Although not indicated in the guidelines as an alternative 23 non-randomized studies and meta-analyzes 24 show that this treatment gives better results than radiotherapy alone. 25 The metaanalyzes show a reduction of up to 35% in the risk of death, and gain of 15% in survival after 5 years, compared to the use of radiotherapy alone.…”
Section: Introductionmentioning
confidence: 99%
“…14,17 It is also observed reversal of intermediate and high risk indicators, such as parametrial invasion, depth of cervical invasion and tumor diameter. 23 The only randomized study comparing this treatment alternative with chemo-sensitization is in patient follow-up phase (EORTC55994/NCT00039338) and its results will be presented in 2018.…”
Section: Introductionmentioning
confidence: 99%